Evaluasi Perencanaan dan Realisasi Anggaran Belanja Pada Sekretariat DPRD Kabupaten Sikka - Maria Reagni Gustiani Sambi; Emilianus Eo Kutu Goo; Yustina Olivia da Silva (Universitas Nusa Nipa Maumere, 2026)
Budget planning and realisation constitute cricital components in ensuring the effectiveness and efficiency of public financial management. This study aims to evaluate the planning and realisation of expenditure budgets at the Secretariat of the Regional House of Representatives in Sikka Regency. The research adopted a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that the budget planning process at the Secretariat of the DPRD in Sikka Regency has been carried out in accordance with applicable procedurse. However, during the realisation phase, several challenges persist, including administrative delays and technical obstacles in activity implementation. Overall, the realisation of the expenditure budget has proceeded with reasonable effectivenees, although improvements are still required in coordination and planning accuracy. Therefore, enhanced planning and optimal supervision are necessary to ensure optimal budget execution.